Izzivi Svetovne trgovinske organizacije v mednarodnem redu - Lindič, Simon (Vojaškošolski zbornik, 2024)
This paper examines the World Trade Organization, its role and importance in the world, and its impact on the international order, highlighting its key achievements and challenges. The role of this organization in the global economy is multidimensional, affecting not only the economic but also the political, social and environmental aspects of the global community. It is one of the key organizations in maintaining a rules-based world order which enables stability and peace, even in the context of contemporary global challenges such as geopolitical tensions and economic fluctuations. The paper explores how the objectives and structure of the WTO have evolved since its inception, and focuses on its current policies and activities, which include trade dispute settlement and ensuring a fair international trading system. A great deal of criticism and challenges, including pressures to adapt to a rapidly changing global environment, call for structural changes and reforms of the organization.
Keywords: global order; global trade; globalna trgovina; Mednarodna trgovina; Mednarodne organizacije; Mednarodni gospodarski odnosi; Mednarodni odnosi; mednarodni red; Svetovna trgovinska organizacija; WTO